Linaclotide: a guanylate cyclase agonist for treatment of irritable bowel syndrome with constipation and chronic constipation in adults - Tikoo, Deepika; Gupta, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2017)
Linaclotide, a 14 aminoacid peptide is an intestinal secretagogue and works by stimulating guanylate cyclase (GC-C) present in the intestinal epithelium, which leads to improvement in symptoms of irritable bowel syndrome with constipation and chronic constipation in adults. Treatments available currently for these gastrointestinal problems have not been very satisfactory and many new options are therefore being explored to provide relief to these patients. Linaclotide has shown promising results in various clinical trials and hence was approved by US Food and Drug Administration (FDA) in 2012.